Feature recognition and classification of shanxi cave dwellings based on deep learning - Jia, Zong; Wan Mohamed, Wan Srihani; Zaky Jaafar, Mohamad Fakri; Ujang, Norsidah (Human Resource Management Academic Research Society, 2023)
Cave dwelling architecture is a unique style of architecture, and it is also the embodiment of Chinese traditional culture in China. It is widely used in the life of working people in ancient China. According to studies, a significant number of people still live in above-ground underground houses and cave dwellings in Australia, Spain, China, Turkey, and Tunisia, and over 40 million people do so in China. However, with the continuous development of society, cave dwellings are gradually unable to meet the needs of more and more people for comparison and work, and tend to be weak. Shanxi cave dwellings have been greatly challenged. Against this background, the aim of this research is to renew and develop cave dwellings better. The research methodology is quantitative method and exploratory research approach. Based on the premise of deep learning to identify and classify the architectural features of Shanxi cave dwellings. In this study, 200 questionnaires were used to measure the residents' requirements for cave dwellings. Through detailed investigation and research on specific examples in Shanxi, the results are as follows: (1) We identify and classify the architectural features of Shanxi cave dwellings based on deep learning algorithm so that we can better understand and explore Shanxi cave dwellings. (2) By analyzing the present situation of examples, it is concluded that most villagers affirm the living comfort and regional adaptability of cave buildings, and the identification and classification of cave building features in Shanxi based on deep learning can provide effective reference, in order to better complete the renovation and development of cave buildings in Shanxi.